Experimental Investigation of Concrete Filled PVC Tube Columns Confined By Plain PVC Socket - Jamaluddin N.; Azeez A. A.; Abd Rahman N.; Attiyah A. N.; Wan Ibrahim M. H.; Mohamad N.; Adnan S. H. (MATEC Web of Conferences, 2017)
This paper presents results of an experimental study for concrete column filled poly vinyl chloride (PVC) tubes confined by plain socket with 5.8 & 6.8 mm thicknesses, 102 mm diameter and 100 mm depth. The total of five concrete filled columns using PVC tubes (CFT PVC) was tested to investigate the columns’ behaviour. The column is 700 mm height, 100 mm external diameter and 3.5 mm tube thickness with different thickness of plain socket. The results presented include maximum axial load, plain socket confinement effect, the mode of failure, and lateral PVC strain. The axial load enhancement of PVC-concrete columns confined using plain socket shows an increment of 21.3% up to 55.2% and axial strain from 21% to 40% compared with displacement for control composite columns at 192 kN ultimate load.